PENERAPAN ALGORITMA ANT COLONY OPTIMIZATION (ACO) PADA JOB SHOP SCHEDULING PROBLEM (JSSP) DI PT. SIEMENS INDONESIA (CILEGON FACTORY) - Widyawati Widyawati (Jurnal Sistem Informasi dan Informatika (Simika), 2018)
Fabrication process is often disrupted by non–deterministic job, this create a problem in the Pre-Fabrication department schedule because often the manufacture of raw material for non-deterministic job should given priority. This problem also affected by the existing system which is not yet fully developed to solve the problem of optimize rescheduling master line (seen from total makespan time). Ant Colony Optimization (ACO) variant Ant System (AS) was proposed to solve Job Shop Scheduling Problem (JSSP) with the objective to propose the best schedule that give shortest makespan. The algorithm tested to perform scheduling of 5 projects (consist of 10 parts) as the initial job, and another 2 projects (consist of 4 parts) as the non-deterministic job. For the initial job, makespan was 287 days and after the arrival of non-deterministic job, makespan was 362 days compare with the actual manufacturing time (7 project consist of 14 parts) which is ± 511 days